The pandemic of online research in times of COVID-19 - Edwin Wouters; Jeroen De Man; Linda Campbell; Hanani Tabana (BMJ Open)
The COVID-19 pandemic has led to an explosion of online research using rating scales. While this approach can be useful, two of the major challenges affecting the quality of this type of research include selection bias and the use of non-validated scales. Online research is prone to various forms of selection bias, including self-selection bias, non-response bias or only reaching specific subgroups. The use of rating scales requires contextually validated scales that meet psychometrical properties such as validity, reliability and—for cross-country comparisons—invariance across settings. We discuss options to prevent or tackle these challenges. Researchers, readers, editors and reviewers need to take a critical stance towards research using this type of methodology.